The Role of Managerial Accounting Information in Enhancing Financial Performance and Decision-Making of Micro Enterprises - Suwandi Suwandi; Ria Manurung; Nodirbek Ibrokhimov (International Forum of Researchers and Lecturers, 2024)
Micro enterprises face significant challenges in financial management, particularly due to the lack of structured financial information and formal accounting systems. Despite the importance of accurate financial data, many micro businesses rely on informal and unreliable financial practices, which can lead to inefficiencies and hinder decision-making. This study aims to assess the impact of managerial accounting information on the financial performance and decision-making processes of micro enterprises. Specifically, it examines how managerial accounting influences financial control, cost efficiency, and profitability. Using a descriptive correlational design, data was collected through interviews with owners and managers of micro enterprises and performance metrics analysis comparing businesses using formal accounting practices with those using informal methods. The findings show that businesses employing managerial accounting systems report better financial control, including more accurate budgeting, cash flow management, and expense tracking. Additionally, the use of managerial accounting techniques leads to improved cost efficiency and profit margins by optimizing resource allocation and reducing unnecessary costs. Interviews revealed that access to accurate financial data significantly enhances decision-making, especially in areas like pricing strategies and investment decisions. However, challenges such as the cost of implementation, complexity, and a lack of financial literacy were identified as barriers to adopting managerial accounting practices in micro enterprises. The study concludes with practical recommendations for micro businesses to integrate managerial accounting into their operations to improve decision-making and financial outcomes, while also suggesting areas for future research into the long-term impact of these practices and the barriers to their implementation.